Serum soluble CD23 levels are an independent predictor of time to first treatment in chronic lymphocytic leukemia. Issue 4 (28th May 2022) - Piñeyroa, Juan A.; Magnano, Laura; Rivero, Andrea; Rivas‐Delgado, Alfredo; Nadeu, Ferran; Correa, Juan Gonzalo; Giné, Eva; Villamor, Neus; Filella, Xavier; Colomer, Dolors; López, Mònica; López‐Oreja, Irene; et al.
Abstract: Serum soluble CD23 (sCD23) levels have been acknowledged as a prognostic factor in patients with chronic lymphocytic leukemia (CLL), but their potential relevance has not been analyzed in recent times. We retrospectively studied 338 CLL, small lymphocytic lymphoma, or CLL‐type monoclonal B‐cell lymphocytosis patients from a single institution, with available sCD23 levels at diagnosis. Baseline features and outcomes were compared between patients with sCD23 ≤/>1000 UI/L. The 140 patients (41%) who had sCD23 > 1000 UI/L showed adverse‐risk clinical and biological characteristics. High sCD23 levels were predictive of a shorter time to first treatment (5‐year probability of requiring treatment: 60 vs. 20%, p  < 0.0001; hazard ratio (HR) = 1.72, p  = 0.003 in a multivariable model also including the CLL International Prognostic Index and the absolute lymphocyte count), and a poorer 5‐year overall survival (70 vs. 82%, p  = 0.0009). These data suggest the potential of sCD23 to predict treatment‐free survival and to shed light on mechanisms of activity and resistance to CD23‐directed therapies.